2016
DOI: 10.1021/acsami.6b07708
|View full text |Cite
|
Sign up to set email alerts
|

In situ Electrochemical Impedance Spectroscopy of Electrostatically Driven Selective Gold Nanoparticle Adsorption on Block Copolymer Lamellae

Abstract: Electrostatic attraction between charged nanoparticles and oppositely charged nanopatterned polymeric films enables tailored structuring of functional nanoscopic surfaces. The bottom-up fabrication of organic/inorganic composites for example bears promising potential toward cheap fabrication of catalysts, optical sensors, and the manufacture of miniaturized electric circuitry. However, only little is known about the time-dependent adsorption behavior and the electronic or ionic charge transfer in the film bulk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…The Bode curve also exhibits the small response time of 0.1 ms and phase angle of approaching 90, which further confirm the good rate performance and conductivity of activated carbon. [27][28][29] Cycling stability text shows after 5000 cycles the specific capacitance can still keep 99% (Figure 2f).…”
Section: Resultsmentioning
confidence: 99%
“…The Bode curve also exhibits the small response time of 0.1 ms and phase angle of approaching 90, which further confirm the good rate performance and conductivity of activated carbon. [27][28][29] Cycling stability text shows after 5000 cycles the specific capacitance can still keep 99% (Figure 2f).…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption of nanoparticles on surfaces follows first-order kinetics as the adsorption depends only on the AuNP concentration. Thus, a first-order exponential function (Equation (4)) is suitable [ 44 , 45 , 46 ] to describe the adsorption process quantitatively. …”
Section: Resultsmentioning
confidence: 99%
“…[104] These authors prepared a thin PS-b-PFS film comprising cylindrical PFS microdomains (20 nm in diameter) on a conductive substrate, and investigated the adsorption of ferritin onto the film using electrochemical quartz crystal microbalance (E-QCM) and AFM. [105] A thin PS-b-P2VP film (50 nm thick) was prepared via spin-coating on gold, followed by exposure to toluene vapor for obtaining lamellar P2VP microdomains oriented perpendicularly to the underlying substrate. AFM images showed selective deposition of ferritin onto the PFS microdomains based on electrostatic attraction with the cationic ferrocenium moieties.…”
Section: Electrochemically-tunable Functional Materialsmentioning
confidence: 99%
“…Subsequently, Wagner et al demonstrated in-situ measurements of the adsorption of negatively-charged AuNPs onto positively-charged microdomains using EIS. [105] A thin PS-b-P2VP film (50 nm thick) was prepared via spin-coating on gold, followed by exposure to toluene vapor for obtaining lamellar P2VP microdomains oriented perpendicularly to the underlying substrate. The P2VP moieties were reacted with alkyl diiodide to gain crosslinked 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 microdomains (40 nm wide) comprising quaternized P2VP moieties.…”
Section: Electrochemically-tunable Functional Materialsmentioning
confidence: 99%